Eco-friendly house purchase decisions among Gen Z: implications for policymakers & housing developers - Sahabudin, Nuradlin Balqis; Haniff, Nurul Izzah Yusmi; Ahmad Taufiq, Muhammad Mukhlis; Mohd Noor, Nurul Hidayana (Universiti Teknologi MARA, Perak, 2025)
A greenhouse, better known as an environmentally friendly house, is a concept that has recently become increasingly popular in society. The innovative design of an eco-friendly house reduces the negative impact on the environment and provides comfort and a better quality of life to the house's occupants. Consumers are a fundamental element that supports the growth of the environmentally friendly home market. Thus, this research aims to discover the factors influencing Generation Z's intention to buy environmentally friendly houses. Using a quantitative approach and survey design, the respondents for this research were 384 prospective home buyers of Generation Z who resided in Negeri Sembilan, Malaysia. Correlational analysis and multiple regression are employed to analyze the final data. This study found that the advertising of eco-friendly houses, attitudes towards eco-friendly houses, perceived environmental responsibility, perceived economic benefits, and perceived social influence positively affect the intention to buy an environmentally friendly house, and the advertising of eco-friendly houses is the most significant predictor. As an implication, more incentives, awareness campaigns, attractive financing options, and effective waste management methods need to be introduced to promote the construction and purchasing of eco-friendly houses as a part of the environmental conservation efforts in Malaysia.